Effect of surface modification by silicon ion beam on microstructure and chemical composition of near-surface layers of titanium nickelide - Psakhie S. G. Sergey Grigorievich; Lotkov A. I.; Meisner S. N.; Meisner L. L.; Sergeev V. P. Viktor Petrovich; Sungatulin A. R. (2013, 2013)
Title screen